2023
DOI: 10.1177/02698811231179801
|View full text |Cite
|
Sign up to set email alerts
|

Psilocybin’s effects on cognition and creativity: A scoping review

Justin N Bonnieux,
Baeleigh VanderZwaag,
Zahra Premji
et al.

Abstract: Background: Research on psilocybin has become increasingly popular during the current psychedelic renaissance, which began in the early 1990s. Psilocybin’s effects on mental health are promising and there are ongoing efforts to investigate its clinical implementation and its effects on cognition. Aims: The purpose of this study is to report trends in publications, methods, and findings from research examining the effects of psilocybin on cognition and creativity in adults. Methods: We conducted an Open Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 116 publications
0
9
0
Order By: Relevance
“…Moreover, the microdosing studies, including a long-term follow-up, showed its neutral and positive effects on cognitive performance. However, the authors did not believe meaningful conclusions could be drawn from these data [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the microdosing studies, including a long-term follow-up, showed its neutral and positive effects on cognitive performance. However, the authors did not believe meaningful conclusions could be drawn from these data [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive examination of psilocybin macrodosing effects on cognition and creativity, elucidated through a scoping review, revealed a time-dependent variation. Initial impairment post-intake was noted, receding over time, with subsequent emergence of positive effects ( Bonnieux et al, 2023 ). However, the controversy surrounding micro-dosing of psilocybin persists.…”
Section: Potential Mechanisms Of Psilocybin Treatment For Admentioning
confidence: 99%
“…Using an alternative approach that captures depression more granularly and comprehensively yields specific insight into areas where psilocybin therapy may be particularly useful to patients and clinicians. Bonnieux et al (2023), review psilocybin's effects on cognition and creativity in a scoping review. The purpose of this study was to report trends in publications, methods and findings from research examining the effects of psilocybin on cognition and creativity in adults.…”
Section: Science Safety and Education: Informing The Psychedelic Trea...mentioning
confidence: 99%